Kesiapan untuk Berubah: Self-Efficacy dan Komitmen Organisasi - Cika Vanny; Ali Jufri; Imam Hadiwibowo; Khalifah Nurjannah; Puspa Dewi Yulianty (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sunan Ampel Surabaya, 2022)
The extreme changes in the global environment and the emergence of the COVID-19 pandemic have created shock and readiness for individual employees and organizations to have a commitment to increase their abilities and knowledge in dealing with changes that occur. PT. Pegadain (Persero) is currently carrying out a transformation that makes every employee need to have self-efficacy and high organizational commitment to support readiness to change. This study aims to determine the effect of self-efficacy and organizational commitment on the readiness to change employees of PT. Pegadaian (Persero) Pegadaian Branch Offices in the Cirebon Region. Respondents in this study were permanent employees of PT. Pegadaian (Persero) Pegadaian Branch Offices in the Cirebon Region, amounting to 80 people. The research method used is multiple linear regression analysis. The results showed that partially thevariable self-efficacy had a positive and significant effect on the readiness to change variable, partially the organizational commitment variable It has a positive and significant effect on the readiness to change variable, and simultaneously thevariables self-efficacy and organizational commitment positive and significant effect on the variable readiness to change employees of PT. Pegadaian (Persero) Pegadaian Branch Offices in the Cirebon Region.